Semi-Immersive Virtual Reality Reduces Pain, Fatiwue and Enhances Comfort and Sleep in Paediatric Oncology - Sumarti Endah Purnamaningsih Maria Margaretha; Iswanti Purwaningsih; Zeni Widiastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pediatric cancer patients undergoing chemotherapy often experience a range of adverse effects, include discomfort, fatigue, pain, and poor sleep quality. These symptoms can have a detrimental effect on the patients’ physical and psychological well-being. Semi-immersive virtual reality (SVR) has emerged as a promising non-pharmacological approach to enhance comfort and reduce treatment-related distress. To examine the effectiveness of SVR in improving comfort, reducing fatigue and pain, and enhancing sleep quality among pediatrics cancer patients undergoing chemotherapy. A quasi-experimental pretest-posttest study was conducted with 52 children aged 6–14 years receiving outpatient chemotherapy. The sampling technique used is using purposive sampling. Instruments included the Pittsburgh Sleep Quality Index (PSQI), Shortened General Comfort Questionnaire (SGCQ), Child Fatigue Scale 24 Hours (CFS-24), and Numeric Rating Scale (NRS) for pain. Data were analyzed descriptively to compare pre-intervention and post-intervention scores. The validity test used was KMO–Bartlett and Factor Loading (EFA), while the reliability test used Cronbach's Alpha. Following the SVR intervention, improvements were observed across all variables. The Pittsburgh Sleep Quality Index (PSQI) improved, with “very poor” decreasing from 31% to 0%, “poor” from 37% to 25%, “fair” increasing from 33% to 63%, and “good” from 0% to 12%. Pain intensity (NRS) decreased, with “moderate” pain dropping from 67% to 0% and “mild” pain increasing from 33% to 100%. Fatigue (CFS) improved: “very high” decreased from 25% to 0%, “high” from 48% to 6%, “moderate” from 27% to 0%, and “low” increased from 0% to 94%. Comfort (SGCQ) increased, with “low” decreasing from 31% to 0%, “medium” from 69% to 50%, and “high” increasing from 0% to 50%. Semi-immersive virtual reality effectively enhances comfort, reduces fatigue and pain, and improves sleep quality among pediatrics cancer patients undergoing chemotherapy. SVR can serve as a complementary, non-pharmacological intervention to support children’s well-being the course of cancer treatment.